(3GdbQGQ GdESJKeGQj aj GdHfhc GdESdGejIs - (3WGjd(B, (3eUWai ceGd GdSjOs ((3GdEScfOQjIs (3GdecJH GdLGeYj GdMOjKs, 2006)
(3GdESJYdGeGJ(B- (3GdMGLI Gdi GdJehjd(B- (3OQGSI WdHGJ GdYedGA GdQGZHjf aj GdJehjd(B- (3GdHfhc GdESdGejI(B- (3OQGSI GdbhGFe GdeGdjI ddefTBJ WGdHI GdJehjd ef GdHfc(B- (3OQGSI GdLOhi GdEbJUGOjI ddeTQhYGJ GdESJKeGQjI GdeWdhH JehjdgG HGdUjZ GdESdGejI Yf WQjb GdHfc GdESdGej(B- (3JfajP GdUjZ GdJehjdjI OGNd GdHfhc GdESdGejI(B- (3eJGHYI JfajP YedjGJ GdJehjd HGdHfhc GdESdGejI(B.s
Keywords: (3GdESJKeGQ GdESdGejs; (3GdHfhc GdESdGejIs